First Mumps Outbreak in a Decade: Measuring Impact of Mumps Among Naïve Population—Tokunoshima Island, Japan. (4th October 2017) - Matsui, Yusuke; Kamiya, Hajime; Kamenosono, Akira; Matsui, Tamano; Oishi, Kazunori; Kidokoro, Minoru; Sunagawa, Tomimasa
Abstract: Background: Currently, mumps vaccine is not included in the routine vaccination program in Japan and consequently, nationwide mumps outbreak is observed approximately every 4 years. Tokunoshima Island, located in the southern part of Japan with population of 25, 000, experienced island-wide mumps outbreak since July 2015. This outbreak was unique because unlike the rest of the country, the Island was not hit by mumps virus for last 10 years. Island being in an inconvenient location, and with less than 2% mumps vaccine coverage rate among one year old children every year, we considered that the population, especially less than 10 years old, is basically naïve to mumps virus. We conducted a comprehensive outbreak investigation to analyze the disease burden of mumps among mumps naïve Island population. Methods: We collected information of epidemiological characteristics for all mumps cases which visited medical facility in the Island from July 1, 2015 to June 30, 2016. In addition, to capture those who developed mumps but not sought medical care, we conducted questionnaire survey targeting all students and their family members. We conducted descriptive analysis to evaluate public health impact of mumps among mumps naïve population. Results: From chart review, we found 1, 191 mumps cases. Median age was 6 years old (range: 0–77). Among them, six cases were tested positive by RT-PCR and its genotype was type G. Genome sequence of the all collected viruses matched 100%. This result indicated that 5.1% of the population developed mumps by a single strain. If we focus on under 10 years old population, the incidence rate is 37, 824 cases per 100, 000 person-years. We also found 24 (2%) cases of aseptic meningitis and 2 (0.2%) cases of deafness. This disease burden is under-estimated as we captured 35 additional cases with symptoms but did not visited medical facility with 61% questionnaire collection rate. Conclusion: We investigated large mumps outbreak which took place in an island with high mumps susceptible population. This disease burden clearly indicates that mumps vaccine should be included in routine vaccination and maintain high coverage rate to prevent periodic outbreaks. Disclosures: All authors: No reported disclosures.